Costs Of Local Government Administration – The Results Of A Pilot Study - Halina Łapińska; Paweł Mrowiec (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The significant elements in the structure of expenditures of local government units (LGUs) are expenditures in the section "Public administration" covering, among others, expenditure on remuneration and derivatives of remuneration. The aim of the paper is to present the results of a pilot study on the administrative costs of local government units. The survey took place in September 2017 and covered one hundred local government units at the basic level, including five cities with district rights. In the units surveyed, the share of administrative costs in total expenditure is diversified, but the lowest occurs in cities with district rights.